تطبيق منهج قاعدة التنازع الدولية على عقود التجارة الالكترونية - يوسفي, نور الدين; بروك, إلياس (revue mofakir, 2018)
The characteristics of e-commerce contracts raise many legal difficulties, related to the suitability of application of the rule of conflict in the field of international, particularly with regard to the legal jurisdiction. In this article we try to highlight the difficulties and legal problems raised by the realization of the approach of conflict if applied to e-commerce, then give a range of solutions and proposals to avoid and overcome these difficulties and problems encountered in the application of the rule of conflict on those transactions.